Thoughts on the Problem of Small Data - Cheng, Jingtao; Chen, Wenhui; Gong, Yuhong (IOP conference series. Materials Science and Engineering, 2018)
Marked by Viktor Mayer-Schönberger's "Big Data: A Revolution That Will Transform How We Live, Work, and Think", Big Data swept across the major subject areas, changing human thinking and behavior. When big data is so hot, "small data" has begun to attract the attention of all sectors of society. Due to the high value of density, deep-level mining, single collection and other significant advantages, in many respects, the infinite value of "small data" is not inferior to big data. This paper focuses on the analysis of the connotation, application and development prospects of "small data", and compares it with "big data", creating a certain reference value for the development and research of small data.